Fundamentals of geophysics. (2nd ed.) - Lowrie, William (Cambridge University Press, 2020)
Preface; 1. The Earth as a planet; 2. Gravity and the figure of the Earth; 3. Seismology and the internal structure of the Earth; 4. Earth's age, thermal and electrical properties; 5. Geomagnetism and paleomagnetism; Index.